Pedagogic solutions and results in designing a mobile game for fire safety teaching - Somerkoski Brita; Tarkkanen Kimmo; Oliva David; Lehto Anttoni; Luimula Mika (Germany, 2025)
It is both expensive, dangerous and partly impossible to practice fire safety scenarios in real environments. Playing a digital game provides us with a view of pupils´ behavior in case of the emergency. In this paper we discuss the pedagogic principles and design approaches followed to develop an AR-based serious game for fire safety. Based on educational sciences, we consider learning as constructed and, as a combination of knowledge, skills and attitudes, which were designed into game mechanics and its pedagogic flow. In the empiric part, we describe the learning outcomes of school aged children before and after the game play. After the game play, school aged children knew the meaning of safety signs better, and they also knew where the signs were located at the school. With the results of this study, we conclude that game-based mobile AR technology can help pupils to learn fire safety issues, increase finding and observing different fire safety signs in their own built environment. As conditions for gaming of this kind are co-development procedures, exact concepts and visuals, authenticity and curriculum-based content of the game.
Proceedings of the 6th International GamiFIN Conference Tampere, Finland, April 26-29, 2022 (Organized as an online conference).